Beyond Digital: Bringing Technology and Value Together in Sharia Fintech - Sirait, Frida Yanti (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2025)
The digital transformation that has taken place in the last decade has changed the face of the global financial system as a whole. Financial technology or fintech has opened up new spaces for financial inclusion, especially for people who were previously unreached by formal financial services. In the context of Muslim society, the presence of sharia fintech is very important because it offers financial services that are not only innovative, but also in line with Islamic values. This research aims to examine in depth how sharia fintech plays a role in answering the challenges of financial inclusion based on Islamic values in the digital economy era. The qualitative approach was used by the method of literature study and in-depth interviews with industry players, academics, and users of sharia fintech. The results of the study show that sharia fintech is not only a technological solution, but also a value movement that brings the spirit of justice, transparency, and blessings in modern financial practices. This study concludes that the success of sharia fintech in expanding financial inclusion depends on the community's sharia financial literacy and regulations that support the principles of sharia maqashid as a whole.